Les migrations transfrontalières au Moyen Âge. Les Occitans en Catalogne Neuve (xiie-xiiie siècles) - Núria Pacheco Catalán (Les Cahiers de Framespa)
During the 12th century, the conquests of the Catalan counties over Al-Andalus accelerated. At the same time, since 1146 the Iberian Peninsula was part of the territories in which the second crusade was taking place. Tortosa, an Al-Andalus city in Catalunya Nova, was one of the first territories that were conquered, in 1148, under the crusaders’ flag. Although the capitulation document stipulated favorable conditions for the Muslim population, only a small portion chose to stay. Consequently, the count granted their goods to the Christian settlers who had participated in the conquest, amongst which were Occitan settlers. The objective of this article is to analyse the role played by the Occitan settlers in the conquest of Catalunya Nova, with a focus on the motivations that led them to migrate and the importance of the border in this matter.